Irritable bowel syndrome is strongly associated with the primary and idiopathic mast cell disorders. Issue 5 (17th September 2021) - Kurin, Michael; Elangovan, Abbinaya; Alikhan, Muhammed Mustafa; Al Dulaijan, Basmah; Silver, Eli; Kaelber, David C.; Cooper, Gregory
Abstract: Background: Mounting evidence supports a mechanistic association between irritable bowel syndrome (IBS) symptoms and mast cell hyperactivity. Yet, association between IBS and mast cell disorders (MCDs) has not been studied. We examined this association using two large databases and verified with manual chart review. Methods: The IBM Watson Health Explorys database (Somers, NY), an aggregate of electronic health record (EHR) data from over two dozen US healthcare systems, and Epic's SlicerDicer tool, a self‐service tool containing de‐identified data from the Epic EHR, were used to identify patients with IBS and MCDs. Patients with organic gastrointestinal disease or diseases associated with secondary mast cell hyperproliferation were excluded. Results were verified with manual chart review from two academic centers. Key Results: Up to 4% of IBS patients had a comorbid MCD. IBS was strongly associated with all MCDs. The strongest association was between IBS and mast cell activation syndrome (OR 16.3; 95% CI 13.1–20.3). Odds ratios for IBS+urticaria, IBS+idiopathic urticaria, IBS+non‐malignant mastocytosis, and IBS+mast cell malignancy ranged from 4.5 to 9.9. Patients from each of these overlap cohorts were predominantly female, and the overlap occurred with all IBS subtypes. Thorough endoscopic evaluation and comorbid mood disorders and migraines are more common in the overlap cohorts than in IBS alone. Conclusions/Inferences: In a large US database encompassing >53 million patients over >20 years, patients with IBS are at least 4 times more likely to have a MCD than the general population. Further study of mast cell involvement in the pathogenesis of IBS is warranted. Abstract :